Viral patriarchy: Discursive mechanisms of gender inequality in TikTok Indonesia’s comment sections - Erfany, Muhammad Nurullah; Arista, Riky (UIN Ar-Raniry Banda Aceh, 2026)
Social media has become a crucial space for producing and disseminating social narratives, including issues of gender inequality and sexuality. TikTok is one of the most popular platforms in Indonesia, widely used by the younger generation. Although studies on gender and digital media generally focus on the representation of women in online content, there remains a limited body of research examining how patriarchal values are reproduced through users’ discursive interactions in social media comment sections. This study analyzes the representation of gender inequality in narratives of sexuality on TikTok Indonesia, focusing on netizens’ responses to content related to gender issues. The study employs a descriptive qualitative approach using content analysis of comments on 10 selected TikTok videos. The findings reveal three main patterns of netizen responses. First, rejection of feminism manifested through misconceptions, stereotypes, and justifications of injustice based on biological and religious arguments. Second, limited support emphasizing principles of human rights and gender equality. Third, ambivalence that nominally accepts equality while maintaining the status quo in social practice. The analysis also identified four mechanisms for reproducing inequality: traditional gender role division, double standards in evaluating sexual behavior, denial of the objectification of women, and the reinforcement of gender hierarchies through narratives of natural order. These narratives are often conveyed through casual language, humor, or religious claims that normalize gender bias. These findings underscore the importance of strengthening digital gender literacy and multistakeholder collaboration to create a more inclusive and gender-sensitive social media ecosystem.